Microencapsulated Comb-Like Polymeric Solid-Solid Phase Change Materials via In-Situ Polymerization - Li, Wei (Polymers (Basel), 2018)
To enhance the thermal stability and permeability resistance, a comb-like polymer with crystallizable side chains was fabricated as solid-solid phase change materials (PCMs) inside the cores of microcapsules and nanocapsules prepared via in-situ polymerization. In this study, the effects on the surface morphology and microstructure of micro/nanocapsules caused by microencapsulating different types of core materials (i.e., n-hexadecane, ethyl hexadecanoate, hexadecyl acrylate and poly(hexadecyl acrylate)) were systematically studied via field emission scanning electron microscope (FE-SEM) and transmission electron microscope (TEM). The confined crystallization behavior of comb-like polymer PCMs cores was investigated via differential scanning calorimeter (DSC). Comparing with low molecular organic PCMs cores, the thermal stability of PCMs microencapsulated comb-like polymer enhanced significantly, and the permeability resistance improved obviously as well. Based on these resultant analysis, the microencapsulated comb-like polymeric PCMs with excellent thermal stability and permeability resistance showed promising foreground in the field of organic solution spun, melt processing and organic coating.